Acid-base properties of solvatochromic pyridinium-N-phenolate betaine dyes in pure and mixed solvents - Mchedlov-Petrossyan, N.O.; Isaenko, Yu.V.; Goga, S.T.; Vilkova, L.N.; Borodenko, V.I.; Shekhovtsov, S.V.; Reichardt, C. (Украинский химический журнал, 2007)
The protonation constants of a set of solvatochromic pyridinium-N-phenolate betaine dyes I–XI (D±) were determined in methanol, water, and the ternary solvent mixture benzene – ethanol – water (with mass ratio 47:47:6) using the vis spectroscopic method. Both, medium effects on transferring from water to organic solvents and salt effects in aqueous media are in agreement with the zwitterionic nature of the betaines, which possess a high dipole moment in the electronic ground state. The character of solvation of dyes D± in the ternary solvent mixture is discussed basing on the position of the charge–transfer (CT) absorption band in the visible region. The association of the betaine dyes with metal ions (Na⁺, Mg²⁺, La³⁺) in 1-butanol manifests itself in a disappearance of the long-wavelength CT band as result of a complex formation with the cationic Lewis acids. Константи протонізації серії сольватохромних піридиній-N-фенолятних бетаїнових барвників (D±) визначено у метанолі, воді та у тернарному розчиннику бензол—етанол—вода (з масовим співвідношенням 47:47:6) за допомогою спектрофотометричного методу. Як ефекти середовища, що спостерігаються при переході від води до метанолу, так і сольові ефекти у водних розчинах узгоджуються з цвіттерйонною будовою бетаїнів, молекули яких мають великий дипольний момент в основному стані. Характер сольватації барвників D± у тернарній суміші розглянуто з урахуванням положення смуги переносу заряду. Асоціація бетаїнів з йонами Na⁺, Mg²⁺ та La³⁺ в 1-бутанолі приводить до зникнення цієї смуги внаслідок створення комплексів з цими кислотами Льюїса. Константы протонизации серии сольватохромных пиридиний-N-фенолятных бетаиновых красителей (D±) определены в метаноле, воде и в тернарном растворителе бензол—этанол—вода (с массовым соотношением 47:47:6) спектрофотометрическим методом. Как эффекты среды, которые наблюдаются при переходе от воды к метанолу, так и солевые эффекты в водных растворах согласуются с цвиттерионным строением бетаинов, молекулы которых имеют большой дипольный момент в основном состоянии. Характер сольватации красителей D± в тернарной смеси рассмотрен с учетом положения полосы переноса заряда. Ассоциация бетаинов с ионами Na⁺, Mg²⁺ и La³⁺ в 1-бутаноле приводит к исчезновению этой полосы вследствие образования комплексов с этими кислотами Льюиса.